Pengaruh CSR Terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Mediasi - Aulia, Desi; Sanusi , Fauji; Mulyani , Ana Susi (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
. This study examines the impact of CSR on firm value using profitability as a mediating variable, to complete this study, a control variable is added, namely firm size. This type of research is quantitative and uses documents from company financial reports, annual reports, and sustainability reports as data collection techniques. The population of this study were companies included in the LQ45 index during the 2016–2023 period, using a purposive sampling technique, so that 19 companies were obtained as samples. The data analysis technique used in the study was path analysis using the Eviews version 12 application and the Sobel test with panel data type. The results of this study indicate that CSR has a significant negative effect on firm value, CSR has a significant positive effect on profitability, profitability has a significant positive effect on firm value, and profitability is able to mediate the effect of CSR on firm value.